(The impact of electronic marketing on the elements of the marketing mix of the banking service (study of banks in the city of Karak - Al Momani, Tayseer Ali Khalaf (Journal of Economic, Administrative and Legal Sciences, 2017)
E-marketing is one of basic contemporary concepts, which has managed during the last few years of the current millennium to jump in all efforts and marketing and various activities to contemporary trends in line with the current era and its variables. The objective of the study is to reveal the role of e-marketing in influencing the elements of the marketing mix of the banking service by using various tools and advanced means and modern technology in the implementation of marketing operations and activities, especially with regard to marketing communications and information technology and the delivery of products as well as the completion of marketing operations through multiple means, making priority to market banking services to various parties through these means. The importance of the study comes from the role of marketing in banking particularly in electronic marketing in achieving the bank's marketing goals through the use of the Internet. The researcher depends on one major hypothesis aims primarily at knowing the impact of electronic marketing on the elements of marketing mix of banking services in commercial banks in Karak, and this study is a theoretical one in which the researcher depends on inductive and deductive methods. One of the most important results of this study that current banking service does not work according to modern trends in electronic marketing, such as the use of computers and other technologies in the production and design of banking services. One of the most important recommendations is the use of electronic devices and equipment in producing, designing and presenting banking services of the sample study as well as the use of electronic marketing techniques in this field because of its positive and enriched impact.
Keywords: E-Marketing; marketing mix banks; banking service